Rachel Carson - Willis, Birdie (Seen : true stories of marginalized trailblazers., 2021)
Chronicles the life of Rachel Carson, the environmentalist who wrote the book "Silent Spring" that sparked the modern-day environmentalist movement and prompted the creation of the U.S. Environmental Protection Agency, and details her early life, career as a biologist and writer, and legacy. Includes a teaching guide with activities and discussion questions.